A novel role for the transcriptional co-activator VITO-1 in skeletal muscle gene regulation - Ayyaswamy, Sriram; Justus Liebig University Giessen (My University, 2014)
Transcriptional regulation in heart and skeletal muscle is controlled by the combined action of 3 major families of transcription factors namely the the bHLH, MADs box transcription factors and the Transcriptional enhancer factor (TEFs) which play important roles for the development of muscle tissues and regulated expression of muscle specific genes. MCAT element (5´-CATTCCT-3´) has been found in a number of cardiac, smooth, and skeletal muscle-specific genes, including cardiac troponin T, beta-myosin heavy chain (beta-MHC), smooth and skeletal muscle -actin. The proteins that bind to the MCAT element belong to the TEF family of transcription factors. VITO-1 was identified as an essential co-factor of TEF1 and activates TEF1 through its SID domain, which results in the transcription of genes involved in muscle cell differentiation. In this thesis, I have analyzed various molecular characteristics of VITO-1 and studied its role in different cell types.To analyze and compare the subcellular localization in different cell types, VITO-1 was over-expressed in HEK 293, C2C12 and CH10T1/2 cell line. VITO-1 displayed a predominant localization in the nucleus of C2C12 and CH10T1/2 cells whereas a cytoplasmic distribution in HEK 293 cells which might be attributed to the absence of endogenous TEFs in this cell line. Co-expression of TEFs with VITO-1 in HEK 293, C2C12 CH10T1/2 cell lines resulted in a complete translocation of VITO-1 into the nucleus. Expression of VITO-1 deletion mutant constructs in C2C12 cells proved the requirement of SID domain to translocate into the nucleus. In the presence of VITO-1, differentiated C2C12 cells formed large myotubes which supports its role in muscle cell formation. To identify additional binding partners of VITO-1, a yeast two hybrid screen was performed with a skeletal muscle cDNA library using the GAL4 system. From a total of 48 positive clones we focused on Telethonin (T-cap) and Myozenin1 (MYOZ1, FATZ) as they were isolated as independent overlapping clones. Telethonin (T-cap) is one of the most abundant transcripts expressed in striated muscle at the Z-discs. MYOZ1 is also a sarcomeric protein that is known to interact with T-cap. The interactions of Tcap and MYOZ1 clones with VITO-1 were reconfirmed using the Y2H assay. An ONPG beta-galactosidase reporter gene assay revealed that VITO-1 binds TEFs with greater efficiency than T-cap and MYOZ1. A failure of Co-IP using the in vitro transcripted / translated proteins to substantiate the interaction between these proteins might be due to the absence of native cellular environment. Since VITO-1 is known to be up regulated in differentiated C2C12 cells and T-cap and MYOZ1 are Z-disc proteins, we used differentiated C2C12 myotubes and chicken primary myocytes for the Co-IP experiments. Indeed VITO-1 containing the SID domain co-immunoprecipitated with Tcapand Myozenin1 in differentiated C2C12 myotubes and primary chicken myocytes thus demonstrating efficient physical interaction. This interaction is mediated through the SID domain as VITO-1 lacking the SID domain did not interact with T-cap and MYOZ1. Immunohistochemistry analysis showed that VITO-1 co-localizes with T-cap in HEK 293 and cos-1 cells. Ectopically expressed VITO-1 was localized both in the nucleus and the Z-discs of neonatal cardiomyocytes. When VITO-1 was co-expressed with T-cap in chicken myocytes, it was localized predominantly at the Z-discs of sarcomeres. A coexpression of VITO-1 with TEF and T-cap in differentiated C2C12 myotubes showed that VITO-1 is distributed both in nucleus as well as cytoplasm. VITO-1 is localized at the nucleus with more intensity where it supposedly interacts with TEF-3 than in the cytoplasm where it might associate with T-cap. This nucleo-cytoplasmic property of VITO-1 needs to be further analyzed. To summarize, the transcriptional co-activator VITO-1 plays a novel role by interacting with the transcriptional machinery (TEFs) as well as the Z-disc (T-cap and MYOZ1) to regulate muscle specific genes.

Die Genexpression in der Skeletalmuskulatur unterliegt hauptsächlich der gemeinsamen Kontrolle von drei Transkriptionsfaktor-Familien (bHLH, MADs and TEFs). Diese spielen eine wichtige Rolle in der Muskelentwicklung und bei der Expression von muskelspezifischen Genen. Das MCAT-Element (5´-CATTCCT-3´) konnte in herzspezifischen Genen, wie Troponin T und in der schweren Kette des beta-Myosins (beta-MHC), sowie in Skelett- und Glattmuskelzellen beta-Aktin nachgewiesen werden. MCAT bindende Protein gehören zur Familie der TEF-transkriptionsfaktoren. Ein essentieller Ko-faktor von TEF1 ist VITO-1. Die SID-Domäne des VITO-1 interagiert mit TEF1 und ist involviert in die Aktivierung von TEF Target-Genen, die verantwortlich für die muskelspezifische Genregulation sind. In dieser Arbeit sollte VITO-1 charakterisiert werden und die funktionelle Rolle von VITO-1 für das myogene Programm untersucht werden.Die Beteiligung von VITO-1 an Prozessen der Muskelzellbildung konnte durch die Ausbildung von großen Myotuben aus differenzierten C2C12-Zellen in Anwesenheit von VITO-1 bestätigt werden. Zur Analyse und zum Vergleich der subzellulären Lokalisation wurde VITO-1 in verschiedenen Zellenlinien überexprimiert. In C2C12- und CH10T1/2-Zellen konnte VITO-1 hauptsächlich im Zellkern nachgewiesen werden. Bei Überexpression in HEK 293-Zellen war VITO-1 jedoch im Zytoplasma lokalisiert, wahrscheinlich aufgrund der niedrigen Konzentration von endogenen TEFs. Die Co-Expression von TEF3 and VITO-1 in HEK-Zellen, sowie in der Zelllinien C2C12 and CH10T1/2 zeigte eine Translokalisation von VITO-1 im Nucleus. Durch ein in C2C12-Zellen eingebrachtes verkürztes VITO-1 Konstrukt konnte nachgewiesen werden, dass die SID-Domäne für diese Translocalisation notwendig ist. Zur Identifizierung weiterer VITO-1 Bindungspartner wurde ein Yeast-two-Hybrid Screen durchgeführt. Insgesamt konnten 48 positive Klone isoliert werden, von denen Telethonin (T-cap) und Myozenin1 (MYOZ1, FATZ) weiter untersucht werden. Die Interaktion der beiden sarkomerischen Proteine Telethonin und MYOZ1 konnte durch die Verwendung eines Y2H-assays bestätigt werden. Durch eine ONPG beta Galactosidase Analyse wurde gezeigt, dass VITO-1 effizienter an TEF3 bindet, als an T-cap oder MYOZ1. Die Interaktionen zwischen VITO-1 und T-Cap, sowie T-Cap und MYOZ1 wurden in vitro nachgewiesen. Hierfür wurden differenzierte C2C12 Myotuben und primäre Myozyten aus dem Huhn verwendet. Es konnte gezeigt werden, das VITO-1 mit T-cap und Myozenin-1 interagiert. Diese Interaktionen sind abhängig von der SIDDomaene von VITO-1. Immunohistochemische Analysen und konfokale Mikroskopie zeigten eine Co-Lokalisation von VITO-1 mit T-cap in HEK 293- und Cos-1 Zellen. Ektopische experimentes VITO-1 war sowohl im Zellkern, als auch in den Z-Banden von murinen neonatalen Kardiomyozyten lokalisiert. Die Koexpression von VITO-1 und Tcap in Myozyten aus dem Huhn war hauptsächlich in den Z-Banden der Sarkomere zu finden, wobei in differenzierten C2C12 Myotuben VITO-1 sowohl im Zytoplasma, als auch im Nukleus nachgewiesen werden konnte. Zur Aufklärung der genauen Funktion von VITO-1 im Nukleus und im Zytoplasma bedarf es weiterer Studien. Zusammenfassend lässt sich sagen, dass VITO-1 durch die Bindung mit Transkriptionsfaktoren (TEFs) und Z-Scheiben-spezifischen Proteinen (T-cap und MYOZ1) eine Rolle bei der Regulation verschiedener muskelspezifischer Gene spielt.
Eine neue Rolle für den transkriptionalen Co-Aktivator VITO-1 bei der Genregulation in der Skelettmuskulatur
Keywords: VITO-1; VGLL2; transcriptional co-activator; skeletal muscle; TEF; ddc:570